2021
DOI: 10.3390/diagnostics11050878
|View full text |Cite
|
Sign up to set email alerts
|

Automated AI-Driven CT Quantification of Lung Disease Predicts Adverse Outcomes in Patients Hospitalized for COVID-19 Pneumonia

Abstract: The purpose of our work was to assess the independent and incremental value of AI-derived quantitative determination of lung lesions extent on initial CT scan for the prediction of clinical deterioration or death in patients hospitalized with COVID-19 pneumonia. 323 consecutive patients (mean age 65 ± 15 years, 192 men), with laboratory-confirmed COVID-19 and an abnormal chest CT scan, were admitted to the hospital between March and December 2020. The extent of consolidation and all lung opacities were quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…A variety of quantitative techniques have been used to quantify COVID-19 infection in the early phase, ranging from simple densitometry to deep learning methods (95,96). Quantitative CT (QCT) assessment of severity of COVID-19 infection in the early phase of infection is an independent predictor of ICU admission and of mortality (97)(98)(99). QCT may also be used to assess sequential change in lung volumes and pulmonary opacity (99).…”
Section: Potential Role For Quantitative Imaging In Post-covid Lung Diseasementioning
confidence: 99%
“…A variety of quantitative techniques have been used to quantify COVID-19 infection in the early phase, ranging from simple densitometry to deep learning methods (95,96). Quantitative CT (QCT) assessment of severity of COVID-19 infection in the early phase of infection is an independent predictor of ICU admission and of mortality (97)(98)(99). QCT may also be used to assess sequential change in lung volumes and pulmonary opacity (99).…”
Section: Potential Role For Quantitative Imaging In Post-covid Lung Diseasementioning
confidence: 99%
“…The pathological abnormalities of mycoplasma pneumonia in children can be seen on a CT scan, and the symptoms can help doctors diagnose patients more accurately 24 . It has been reported that Clinical worsening or mortality in patients with COVID-19 pneumonia can be predicted using a quantitative assessment of the radiological extent and severity of lung illness utilizing an autonomous 3D AI-based software 25 . However, the quantitative assessment of CT features of MPP by AI software has not been reported extensively.…”
Section: Discussionmentioning
confidence: 99%
“…To appraise COVID-19 infection in the initial phase, different techniques are used, including densitometry and deep learning methods [ 30 , 31 ]. Early phase quantitative CT assessment of severity is an autonomous forecaster of ICU hospitalization and mortality [ [32] , [33] , [34] ]. It could as well be used to appraise serial variations in lung volumes and pulmonary opacity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%